2016
DOI: 10.1142/s0218271816500966
|View full text |Cite
|
Sign up to set email alerts
|

On the electrodynamics of moving particles in a quasi flat spacetime with Lorentz violation and its cosmological implications

Abstract: This research aims to develop a new approach towards a consistent coupling of electromagnetic and gravitational fields, by using an electron that couples with a weak gravitational potential by means of its electromagnetic field. To accomplish this, we must first build a new model which provides the electromagnetic nature of both the mass and the energy of the electron, and which is implemented with the idea of γ-photon decay into an electron-positron pair. After this, we place the electron (or positron) in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…As we realize, the shrinkage of the proton radius is consequence of the interactions of electric charges (of the quarks with rotation) and the n(o)-flux. In another paper published by Guglinski, to published later, it is shown that the growth of the mass of particles (by following the Lorentz factor, as proposed by Einstein) is promoted by the interaction between electric charges of elementary particles and the gravitons existing in the space filled by the aether, corroborating what is proposed in (Cruz, 2016), but Guglinski's paper introduces an additional argument, because Nassif's theory is unable to explain why neutral pions and the neutron have mass, in spite of they have no charge. Therefore, the shrinkage of the proton radius and the growth of mass by Lorentz factor, are both under the rule of the law of interaction between electricitons and gravitons.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…As we realize, the shrinkage of the proton radius is consequence of the interactions of electric charges (of the quarks with rotation) and the n(o)-flux. In another paper published by Guglinski, to published later, it is shown that the growth of the mass of particles (by following the Lorentz factor, as proposed by Einstein) is promoted by the interaction between electric charges of elementary particles and the gravitons existing in the space filled by the aether, corroborating what is proposed in (Cruz, 2016), but Guglinski's paper introduces an additional argument, because Nassif's theory is unable to explain why neutral pions and the neutron have mass, in spite of they have no charge. Therefore, the shrinkage of the proton radius and the growth of mass by Lorentz factor, are both under the rule of the law of interaction between electricitons and gravitons.…”
supporting
confidence: 71%
“…And Einstein decided to sacrifice Galileo. However, the immolation of Galileo was not enough, because nowadays new experiments are suggesting that Maxwell equations can be incomplete, and what is missing in his equations obviously has reflection in QED, as shown in several papers (Cruz, 2016;Cláudio Nassif, 2008;Claudio Nassif, 2010;Cláudio Nassif, 2012, 2015. Curiously Einstein had interpreted wrongly the meaning of the negative result in the Michelson-Morley experiment, because at that time he and the theorists had supposed that the nature of the light is undulatory, i.e., that light is a wave moving in the aether, and such supposal requires that Michelson's interferometer would have to detect a difference in his experiment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown in a paper that the vacuum permeability and permittivity may originate from the magnetization and the polarization of continuously appearing and disappearing fermion pairs of the vacuum (Urban, Couchot, Sarazin, & Djannati-Atai, 2013). Several experimental findings, published along the last 15 years, are suggesting that the space is no empty (Wilson et al, 2011), and we are suggested to suppose that the quantum vacuum has a physical structure, formed by particles of a new sort of aether, different of that old classical luminiferous-aether imagined in the 19 th Century: a new non-luminiferous aether (Cruz, 2016). Concerning such controversial subject, the aether, since 1919 the physicists have neglected, it seems purposely, an historical fact, and along several decades it was even forgotten for many generations of physicists.…”
Section: Physical Structure Of Electric Fields Of the Proton And Elecmentioning
confidence: 86%